Evaluating effects of the structural reform of outpatient psychotherapy for patients with mental disorders in Germany: comparing patients with and without comorbid chronic physical condition$drationale and study protocol of the ES-RiP project - Kampling, Hanna; Kruse, Johannes; Friederich, Hans-Christoph; Heuft, Gereon; Christoffer, Andrea; Grobe, Thomas G.; Marschall, Ursula; Szecsenyi, Joachim; Wild, Beate; Hartmann, Mechthild (BMJ open, 2022)
Introduction In 2017, in Germany, a structural reform of the outpatient psychotherapy guideline took place, aiming to reduce waiting times, to facilitate flexible low-threshold access (eg, general reachability by phone) and to lower access barriers for specific patient groups. The reform included new service elements, such as the implementation of additional psychotherapeutic consultations, acute short-term psychotherapeutic interventions and relapse prophylaxis as well as the promotion of group therapies, the facilitation of psychotherapists’ availability, and the installation of appointment service centres. The ES-RiP project aims to thoroughly evaluate the effects of the reform with a special focus on patients with a comorbidity of mental disorders and chronic physical conditions (cMPs) compared with patients with a mental disorder but no long-term physical condition (MnoP). The project aims to evaluate (a) the extent to which the reform goals were achieved in the large group of patients with cMPs compared with MnoP, (b) the barriers that might hinder the implementation of the new guideline and (c) the procedures required for further developing and improving outpatient psychotherapy. - Methods and analysis A mixed-methods design (quantitative, qualitative) along with a multilevel approach (patients, service providers, payers) triangulating several data sources (primary and secondary data) will be applied to evaluate the reform from different perspectives. - Ethics and dissemination Ethical approval was obtained from the coordinating committee as well as one local ethics committee, Justus Liebig University Giessen and Marburg - Faculty of Medicine (approval number: AZ 107/20) and Heidelberg (approval number: S-466/2020). The results of this study will be disseminated through expert panels, conference presentations and publications in peer-reviewed journals. - Trial registration number DRKS00020344.
Gesehen am 24.10.2022